2010
DOI: 10.1007/s11431-010-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Constructal optimization of discrete and continuous-variable cross-section conducting path based on entransy dissipation rate minimization

Abstract: Using constructal entransy dissipation rate minimization method based on discrete variable cross-section conducting path, constructal optimizations of elemental area with variable cross-section conducting path are performed, and the results are compared with the optimization results of elemental area with the constant cross-section conducting path. The comparison shows that the minimum mean temperature difference based on elemental area with variable cross-section conducting path increases and approaches a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…[154]. (6) The process of constructal optimization based on variable cross-section shape and variable high conducting path element is shown in Figure 17 [155].…”
Section: Figure 16mentioning
confidence: 99%
“…[154]. (6) The process of constructal optimization based on variable cross-section shape and variable high conducting path element is shown in Figure 17 [155].…”
Section: Figure 16mentioning
confidence: 99%
“…Based on the concept of entransy dissipation, Guo et al [4] developed the extremum entransy dissipation principle, defined the entransy-dissipation-based thermal resistance, and proposed the minimum thermal resistance principle. It was found that the principles of the entransy theory are appropriate to the optimization of heat conduction [5][6][7][8][9][10][11][12][13], heat convection [14][15][16][17], thermal radiation, design of heat exchangers [21][22][23][24][25][26][27] and phase change heat transfer processes [28]. Eqs.…”
mentioning
confidence: 99%
“…With the concept of entransy dissipation or thermal resistance based on entransy dissipation, researchers have conducted many optimization studies of heat conduction, heat convection and mass convection [17][18][19][20][21][22][23]. Chen and co-authors [21][22][23] combined the extremum entransy dissipation principle with the constructal theory and optimized many heat transfer systems based on entransy dissipation rate minimization. In researches of heat exchangers and HENs, Song et al [24] demonstrated the uniformity principle of temperature difference field for one-dimensional heat exchanger based on the extremum entransy dissipation principle.…”
mentioning
confidence: 99%